Thermal Performance of Apartment (High-Rise) in Surabaya with Precast Concrete for the Building Envelope - Romanria Violina Mahardhika; Ima Defiana; V. Totok Noerwasito (Institut Teknologi Sepuluh Nopember, 2014)
Lack of horizontal land causes the development of vertical buildings. Residences in major cities are dominated by apartments from the low rise to the high rise types. Based on the information cited from Vivanews May 2, 2010, the number of apartments in Surabaya approximately 12 new apartment projects and has been built with a total of 5,000 units with an average of nearly 80% is sold in every apartment. Current sheath material that is widely used for apartment’s envelope is precast concrete. Precast concrete is the material that had been made at the factory in accordance with the form of the mold, then the molded concrete will be transported and installed to the building construction site. Precast concrete is chosen because it has several advantages when compared to conventional concrete structural system, including the efficiency of processing time, energy efficiency, and environmentally friendly. Given these statements, the researcher needs to know the thermal performance of apartment buildings (high-rise) in Surabaya with precast concrete building envelope. Expected to know the configuration of precast concrete materials in the building envelope, the researcher can construct an apartment building design proposals that meet the criteria of thermal comfort in tropical regions. This study aims to identify and explain the thermal performance of the precast concrete configuration in apartment buildings (high-rise) in Surabaya for the buiding envelope. The method that is used for this research is an experimental method to study the object with modeling strategies by Archipak for the simulation. The results shows that thermal performance of precast concrete pretty well applied to the apartment with thermal properties that support the value of the thermal performance of precast.